Can public health services promote the settlement intention of migrant workers: empirical analysis from China - Lyu, Tong (Frontiers in Public Health, 2024)
IntroductionEnhancing migrant workers’ settlement intention in cities requires ensuring they have equal public health rights as urban residents. Full access to public health services can strengthen their sense of belonging and improve the well-being of this vulnerable group. Evaluating the welfare impact of public health services from the perspective of city identification offers valuable insights and informs policies aimed at improving the quality of public health service provision.MethodsThis study utilizes data from the 2017 China CMDS survey. We employed various analytical methods, including the Probit model, IV-Probit model, Propensity Score Matching, and KHB decomposition, to empirically examine the impact of public health services on the settlement intention of migrant workers. Additionally, we explored the underlying mechanisms and heterogeneity of this impact.ResultsPublic health services such as health records management and public health education significantly increase the settlement intention of migrant workers. The positive effect of public health services on the settlement intention is more pronounced among migrant workers who have moved across provinces and those who are married. Public health services indirectly enhance the settlement intention by improving urban satisfaction and sense of belonging, with the latter having a more substantial indirect effect.DiscussionThe current provision of basic public health services in China for migrant workers still needs improvement. This highlights the necessity of enhancing health record management, increasing health education and training, and tailoring services to better meet the needs of migrant workers. By improving the supply of public health services, we can effectively raise migrant workers’ urban satisfaction and sense of belonging, thereby indirectly increasing their willingness to settle in cities. The findings of this study contribute to further optimizing the implementation of public health service policies and provide meaningful guidance for improving the urban integration of migrant workers.